Analisis Penerapan Manajemen Waktu pada Proyek Gedung Apartemen Four Seasons Jakarta - Vira Nur Aulia Rahm; Rizki Achmad Darajatun (Peneliti.net, 2022)
Time management has an important role in a project. With good time management projects can be carried out on time, quality, and cost. The potential that may occur if time management does not run well is a waste of costs, quality that does not meet consumer expectations, and completion time exceeding estimates. This study aims to analyze the time management applied by PT. Praja Vita Mulia in the construction project of the Four Seasons Jakarta Building. Descriptive qualitative analysis method is used to describing every element in time management, such as existing activities, activity sequences, duration estimation, scheduling, and project control. After describing clearly then made a comparison of the actual conditions with the existing theory. Sources of research data obtained through literature studies and field studies. From the results of the analysis it can be concluded that the time management applied to the development project has been going well so that every activity in the project can be completed on time without significant obstacles.